Interaction in parents' family as a factor of orientation of financial behavior - Chigire, О. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article deals with problem of the economical direction selection by young people caused with features of interpersonal relations in parental families.
Keywords: financial behavior; economical direction type; interpersonal relations in parental families; entrepreneur; freelancer; manager